Ludic Prognostication: Games as Sites for Simulating the Future - Deshbandhu, Aditya (Gamevironments, 2022)
This article examines if video games can be used to simulate future scenarios by charting the intersections of game studies, science fiction studies, and simulation. By analyzing games that are set in futuristic societies as sites that can be used to address concerns for the future, this article argues that video games’ unique form and structure as meta-media artifacts makes them an ideal site for simulating, showcasing, and experiencing possible trajectories of the future. This article builds on this argument by examining three games, namely Deus Ex: Mankind Divided (2016), Detroit: Become Human (2018), and Cyberpunk 2077 (2020), as texts and as ludo-narratological experiences. The futuristic realities put forth in the three games are examined using close-reading, formal game analysis, and an autoethnographic analysis of specific ludic experiences. This article looks at how games can simulate specific trajectories of the future by examining the various dimensions of socio-cultural interactions that are explicitly and implicitly presented in these game worlds. The subsequent analysis also reveals how issues of equality, identity, gender, religion, and the human body will most likely shape key points of contestation for humanity as it single-mindedly continues to chase a techno-utopian reality.